Simulation of High Efficiency CIGS Solar Cells with SCAPS-1D Software. (August 2015) - Mostefaoui, M.; Mazari, H.; Khelifi, S.; Bouraiou, A.; Dabou, R.
Abstract: In this paper, the high efficiency Cu(In, Ga)Se2 (CIGS)-based solar cells solar cells was analyzed and designed by SCAPS-1D software. This paper deals with the influence of a buffer layer on the performance of the CIGS-based solar cells. The photovoltaic parameters have been calculated in different buffer layer materials (CdS, ZnS, ZnSe), we give great alternative for Cadmium sulphide (CdS). Starting with a good structure, we simulated the J-V characteristics and showed how the absorber and buffer layers thickness, defect density influence the short-circuit current density (Jsc ), open-circuit voltage (Vco ), fill factor (FF), and efficiency (η) of solar cell. The optimized solar cell shows an efficiency of > 22% under the AM1.5G spectrum and one sun.